Book Reviews - Zotova, Natalia; Tilbe, Fethiye; Thakker, Mansi; Gulina, Olga R.; Knapton, Samantha (Migration Letters, 2015)
Kibria, N.; Bowman, C., and O’Leary, M. (2014). Race and Immigration. Cambridge: Polity Press. 297 pages. (ISBN: 9780745647913) Vollmer, B. A. (2014) Policy Discourses on Irregular Migration in Germany and the United Kingdom. London: Palgrave Macmillan, 297 pages. (ISBN: 9781137307552) Biradavolu, M. R. (2008) Indian Entrepreneurs in Silicon Valley, the Making of a Transnational Techno-Capitalist Class. Cambria Press, 237p. (ISBN: 9781604795277) Sirkeci, I., Elcin, D., Seker, G. (ed.) (2015) Politics and Law in Turkish Migration. London, UK: Transnational Press London, 190p. (ISBN: 978-1-910781-00-5) Hackett, S. (2013) Foreigners, Minorities and Integration: The Muslim Immigrant Experience in Britain and Germany. Manchester: Manchester University Press, 277 pages. (ISBN – 978-0-7190-8317-4)